Peningkatan pengetahuan masyarakat tentang perlindungan anak dari aspek pendidikan, hukum, dan kesehatan di Desa Tambun Kecamatan Bandar Petalangan - Ulfia Hasanah; Hayatul Ismi; Ihda Hasbiyati; Maimunah Maimunah; Rismadefi Woferst; Yenni Kusumawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
There are several problems in the community with children in the fields of Education, Law and Health. There are still children under 18 years of age who are exploited as commercial sexual workers; children in conflict with the law, children aged 10-18 Years work in the informal sector, children who leave primary school before graduating or do not continue to the next level due to access and economy; adoption cases are carried out outside the standard population administration procedures; the discovery of stunted children. So, it is necessary to increase public understanding regarding child protection. One of those who have the responsibility of providing protection to children is the parent, the service program is carried out by providing material related to the role of parents and society in providing protection to children. The delivery of this material aims to provide an understanding of child protection in terms of education, law and health so that the public can understand the importance of protecting children. This service activity in Tambun Village can be said to be successful. There was a request from the participants to continue this activity. The people of Tambun Village hope that for further activities, further training is given regarding the skills needed by parents and the community. To increase community understanding, the WA Group was also created, whose members are parents who have participated in the Socialization program, this group aims to be a forum for communication between the Service Team and the local community.